Minor psychiatric disorders among university students during the COVID-19 pandemic - Luciane Prado Kantorski; Ariane da Cruz Guedes; Aline Neutzling Brum; Carlos Alberto dos Santos Treichel; Vinícius Boldt dos Santos; Bianca Albuquerque Gonçalves; Mariana Dias Almeida (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To identify the prevalence and factors associated with the manifestation of Minor Psychiatric Disorders (MPD) among university students in southern Brazil during the COVID-19 pandemic. Method: Cross-sectional study, conducted in August and September 2020, with 464 university students. The Self-Reporting Questionnaire (SRQ-20) was used with a cut-off point ≥ 7, and associated factors were identified through crude and adjusted analyses using logistic regression. Results: The prevalence of MPD was 76.5%. Factors positively associated with the outcome were female gender, job loss during the pandemic, use of psychoactive substances, and difficulties in following online classes. Being in social distancing for seven months or more was negatively associated with the outcome. Conclusion: High prevalence of MPD among the studied sample, as well as a relationship between this outcome and the consequences of the COVID-19 pandemic.